Daily adjunctive therapy with vitamin D3 and phenylbutyrate supports clinical recovery from pulmonary tuberculosis: a randomized controlled trial in Ethiopia. (23rd May 2018) - Bekele, A.; Gebreselassie, N.; Ashenafi, S.; Kassa, E.; Aseffa, G.; Amogne, W.; Getachew, M.; Aseffa, A.; Worku, A.; Raqib, R.; Agerberth, B.; Hammar, U.; et al.
Abstract: Objective: Immunotherapy using vitamin D (vitD3 ) and phenylbutyrate (PBA) may support standard drug regimens used to treat infectious diseases. We investigated if vitD3 + PBA enhanced clinical recovery from pulmonary tuberculosis (TB). Methods: A randomized controlled trial was conducted in Addis Ababa, Ethiopia. Patients with smear‐positive or smear‐negative TB received daily oral supplementation with 5000 IU vitD3 and 2 × 500 mg PBA or placebo for 16 weeks, together with 6‐month chemotherapy. Primary end‐point: reduction of a clinical composite TB score at week 8 compared with baseline using modified intention‐to‐treat (mITT, n = 348) and per‐protocol ( n = 296) analyses. Secondary end‐points: primary and modified TB scores (week 0, 4, 8, 16, 24), sputum conversion, radiological findings and plasma 25(OH)D3 concentrations. Results: Most subjects had low baseline plasma 25(OH)D3 levels that increased gradually in the vitD3 + PBA group compared with placebo ( P < 0.0001) from week 0 to 16 (mean 34.7 vs. 127.4 nmol L −1 ). In the adjusted mITT analysis, the primary TB score was significantly reduced in the intervention group at week 8 (−0.52, 95% CI −0.93, −0.10; P = 0.015) while the modified TB score was reduced at week 8 (−0.58, 95% CI −1.02, −0.14; P = 0.01) and 16 (−0.34, 95% CI −0.64, −0.03; P = 0.03). VitD3 + PBA had no effect on longitudinal sputum‐smear conversion ( P = 0.98). Clinical adverse events were more common in the placebo group (24.3%) compared with the vitD3 + PBA group (12.6%). Conclusion: Daily supplementation with vitD3 + PBA may ameliorate clinical TB symptoms and disease‐specific complications, while the intervention had no effect on bacterial clearance in sputum. Abstract : Click here to view the Editorial Comment by Dr. Wejse